1937–1938 m. Didžiojo teroro „vykdytojų“ fenomenas - Podkur, Roman (Genocidas ir rezistencija, 2023)
The article examines the phenomenon of “performers” during the Great Terror of 1937–1938 in Ukrainian historiography of the mid-1990s – 2020s is studied. Research methodology and methods. Exploring the principles of historicism, systematicity, objectivity, comprehensiveness, and continuity, the author reveals their dependency on the origin of historical knowledge. The factor of subjectivity (the researcher’s personality) is particularly determining and obstructing objectivity of the research. The author employed istoriographical analysis, synthesis, typology of research directions, and comparative analysis. Conclusions. The study of the phenomenon of the “perpetrator” of the Great Terror became possible only after the complete eclassification of the documents of the communist special services. The study of the phenomenon had a certain dynamic – from the role of the “general director of terror” Joseph Stalin, his closest entourage, the people’s commissars of Internal affairs of the USSR and Soviet Ukraine to the activities of specific investigators of the regional Ukrainian NKVD, heads of district apparatuses, direct executioners of death sentences. The researchers were able to outline the overall portrait of the performer: Chekist-organizer, Chekist-investigator, Chekist-executioner. Researchers have identified some patterns of Chekists’ behaviour when accused of “violating socialist legality” by the top political leadership. The patterns indicate attempts to avoid or reduce punishment, to not openly accuse Stalin and the higher party-Soviet leadership of forcing them to commit the crime. This shows that criticism of the Communist Party was inadmissible in their corporate worldview. Such a tendency was characteristic of the Soviet security organs throughout the life of the communist regime.